PENGARUH KONSENTRASI BUAH JAMBU BIJI MERAH TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK FRUIT LEATHER PULPKULIT DURIAN - JAMBU BIJI MERAH - Putro, Candra Adi; Surjoseputro, Sutarjo; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2015)
Fruit leather can be made from the pulp of durian skin. Making fruit leather pulp of durian skin has a weakness that has no taste and flavor as well as color less attractive so that material needs to be added with a strong flavor and color from the outside. One of them is with the addition of guava fruit. The concentration guava red give you different characteristics of texture, color, and flavor leather is produced. The research was done to determine the effect of concentration red guava on physicochemical and organoleptic leather pulp of durian skin red guava. The research design used was the RAK (Random Design Group) non factorial factors examined were the concentration red guava that consists of 6 (six) in the form of 10% (b/b); 20% (b/b); 30% (b/b); 40% (b/b); 50% (b/b); 60% (b/b), and repeated treatment level as many as four (4) times. The parameters tested included the physicochemical (moisture content, aw, texture (flexibility), pH, and color) and organoleptic (a fondness for taste, texture, and color). The use of red guava increased aw, moisture content, texture (flexibility), redness, on the other hand decreasing the value of pH, lightness, and yellowness of leather. The best concentration of red guava was at 40% which had pH 3.16, aw0.60, moisture content 17.35%, texture (flexibility) 36.73 N/s, lightness 43.36, redness 26.21, and yellowness 21.35 with sensory scores for flavor, texture and color were 4.59, 4.58, and 5.24 respectively with scoring 1-7.